2020
DOI: 10.37742/jpoe.v2i2.58
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh gaya mengajar dan kemampuan motorik terhadap hasil belajar forehand drive tenis meja

Abstract: Tujuan penelitian ini untuk memperoleh informasi tentang pengaruh gaya mengajar dan kemampuan motorik  terhadap hasil belajar forehand drive tenis meja di SMP Negeri 1 Saguling. Metode penelitian ini adalah eksperimen,  Populasi siswa kelas VIII SMPN 1 Saguling berjumlah 75siswa, sampel yang digunakan adalah 40 orang , dengan teknik pengambilan sampel menggunakan pengambilan purporsif sampling dari keseluruhan populasi penelitian 100%. Dari total populasi kemudian diukur sebanyak 27% kelompok atas dan bawah se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
0
0
3
Order By: Relevance
“…These results showed that children's gross motor skills improved after treatment, namely a TGfU approach. Based on the results of these findings, it can be interpreted that the importance of taking the TGfU approach in motion learning, especially in gross motor learning, is in line with previous findings that an appropriate motion learning approach or exercise will have an impact on the desired results (Hasmarita & Kurnia, 2020). From the explanation above, it can be indicated that TGfU can improve the child's gross motor with the increasing gross motor of the child, which can contribute to the child's growth.…”
Section: Discussionsupporting
confidence: 85%
“…These results showed that children's gross motor skills improved after treatment, namely a TGfU approach. Based on the results of these findings, it can be interpreted that the importance of taking the TGfU approach in motion learning, especially in gross motor learning, is in line with previous findings that an appropriate motion learning approach or exercise will have an impact on the desired results (Hasmarita & Kurnia, 2020). From the explanation above, it can be indicated that TGfU can improve the child's gross motor with the increasing gross motor of the child, which can contribute to the child's growth.…”
Section: Discussionsupporting
confidence: 85%
“…Semakin baik servis yang dilakaukan, semakin keras, dan semakin tajam, serta semakin mengecoh sebuah servis maka akan semakin besar pula kemungkinan sebuah servis tersebut menjadi sebuah point atau sebuah angka untuk memperoleh kemenangan (Hasmarita & Kurnia, 2020;Wani, 2020). Ada banyak cara yang digunakan oleh para pelatih untuk melatih para pemainnya mampu menguasai tekhnik servis forehand dan backhand (Indrawan et al, 2019;Lestari et al, 2019).…”
Section: Pendahuluanunclassified
“…Dengan melakukan passing yang baik dalam suatu permainan maka strategi bertahan dan menyerang yang diharapkan dapat dipraktikan dengan sebaikbaiknya. maka dapat di asumsikan bahwa dalam perkembangan pendidikan jasmani ser ingkali kurang teraktualisasi dengan baik (Hasmarita & Kurnia, 2020).…”
unclassified